PENGEMBANGAN PERMAINAN ANSWER AND JUMP SEBAGAI UPAYA PENCEGAHAN PELECEHAN SEKSUAL PADA ANAK USIA 4-5 TAHUN - Salsabillah, Irsalyna; Yudianti, Ika; Cahyani, Desy Dwi (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2025)
Early childhood often experiences various forms of physical, verbal, mental, and sexual violence that can interfere with their development. Data from the Malang Regency Women's Empowerment and Child Protection Service in 2023 recorded that the number of victims of sexual violence against children increased twofold due to children's lack of understanding of sex education. This study aims to develop the Answer and Jump game as an educational media to prevent sexual harassment in children aged 4-5 years. The method used is Research & Development research with 10 steps of development procedures, (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Trial, (7) Product Revision, (8) Usage Trial, (9) Product Revision, (10) Mass Production. Of the 10 steps, the researcher carried out up to step 7 with a sample of 18 children aged 4-5 years at the Mutiara Bunda PAUD Post, Malang City. The research instrument used a product assessment questionnaire. The results of the study showed that the developed media was categorized as very feasible, with assessments from material experts (92%), media experts (98%), and user responses (87%). Thus, the Answer and Jump game is feasible to use, but further testing is needed on wider and more diverse groups.